2008
DOI: 10.1161/circulationaha.107.707661
|View full text |Cite
|
Sign up to set email alerts
|

Utility of Cardiac Monitoring in Fetuses at Risk for Congenital Heart Block

Abstract: Background-Anti-SSA/Ro-associated third-degree congenital heart block is irreversible, prompting a search for early markers and effective therapy. Methods and Results-One hundred twenty-seven pregnant women with anti-SSA/Ro antibodies were enrolled; 95 completed an evaluable course in 98 pregnancies. The protocol included fetal echocardiograms performed weekly from 16 to 26 weeks' gestation and biweekly from 26 to 34 weeks. PR intervals Ͼ150 ms were considered prolonged, consistent with first-degree block. Nin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
124
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 274 publications
(134 citation statements)
references
References 40 publications
1
124
0
1
Order By: Relevance
“…Cord blood samples and ELISA for erythropoietin. Cord blood samples were obtained at birth from family members enrolled in the Research Registry for Neonatal Lupus (14) as well as the PR Interval and Dexamethasone Evaluation in CHB Study (15). For inclusion in the present study, a child was considered to have CHB if the following 2 criteria were met: 1) presence of heart block (first-, second-, or third-degree) documented by electrocardiogram, echocardiogram, history of pacemaker, or statement in the medical record; and 2) presence of antibodies to SSA/Ro in the maternal serum, as determined by commercial ELISA (Diamedix, Miami, FL), ELISA with recombinant proteins, and/or SDS immunoblotting to identify the fine specificity of the autoantibody response.…”
Section: Hypoxia Fibrosis and Congenital Heart Block 4123mentioning
confidence: 99%
“…Cord blood samples and ELISA for erythropoietin. Cord blood samples were obtained at birth from family members enrolled in the Research Registry for Neonatal Lupus (14) as well as the PR Interval and Dexamethasone Evaluation in CHB Study (15). For inclusion in the present study, a child was considered to have CHB if the following 2 criteria were met: 1) presence of heart block (first-, second-, or third-degree) documented by electrocardiogram, echocardiogram, history of pacemaker, or statement in the medical record; and 2) presence of antibodies to SSA/Ro in the maternal serum, as determined by commercial ELISA (Diamedix, Miami, FL), ELISA with recombinant proteins, and/or SDS immunoblotting to identify the fine specificity of the autoantibody response.…”
Section: Hypoxia Fibrosis and Congenital Heart Block 4123mentioning
confidence: 99%
“…Eight foetuses had signs of 1st degree block. It is of note that the cut-offs for 1st degree block were lower than those reported by Friedman [29]. One of these foetuses (whose PR interval was abnormal in the Swedish study but would not have been considered abnormal in the US study) had progression to complete block, and another showed recovery from 2nd degree block to 1st degree block, with betamethasone treatment.…”
Section: Assessment Of First Degree Av Block In Uteromentioning
confidence: 55%
“…Also, the American group did not find any prolongation of QT interval in a prospective study of 98 infants, but in this study, a control group was lacking [29]. Thus, overall, QT prolongation as a consequence of autoantibody injury remains unproven.…”
Section: Qt Interval Prolongationmentioning
confidence: 56%
See 2 more Smart Citations